Blue willow - Gates, Doris 1901-; Lantz, Paul 1908- (New York Puffin Books, 1968)
A little girl, who wants most of all to have a real home and to go to a regular school, hopes that the valley her family has come to, which so resembles the pattern on her treasured blue willow plate, will be their permanent home.
Keywords: Migrant labor -- Fiction